Uncovering the Listeria monocytogenes virulence traits - Camargo, Anderson Carlos (2017)
Listeria monocytogenes is a Gram-positive bacterium commonly isolated from food processing environment, raw and processed foods. It is recognized as the causative agent of listeriosis, a serious disease that affects mainly individuals from risk groups. The present study aimed to characterize L. monocytogenes isolates recovered in Brazil from clinical sources, meat processing environmental and beef. Antibiotic resistance profiles, virulence genes, serotype diversity, ability to invade, replicate and spread in host cells, as well as cell death and IFN production induced by L. monocytogenes isolates were characterized. All isolates presented sensitivity to antimicrobials used for listeriosis treatment while most of them presented resistance or intermediate resistance to clindamycin and oxacillin. Molecular serogrouping produced contradictory results for seven isolated from serotype 1/2a, which were positive for the gene lmo1118 and exhibited the profile IIc (serotypes 1/2c or 3c). In addition, fifteen isolates from serotype 4b amplified the gene lmo0737, being classified as atypical IVb-v1. The potential to invade Caco-2 cells was significantly affected by the presence of premature stop codons (PMSCs) in inlA gene of isolates from serotype 1/2c (p < 0.005). The isolates varied widely in their intracellular doubling times, and there was no clear relationship between serotype or source. There were significant differences between serotypes for cell-to-cell spread in Caco-2 cells, isolates from serotype 1/2a were generally impaired in their spreading ability while most os isolates from serotype 1/2b exhibited increased spreading ability (p < 0.0001). In addition, we identified three isolates from serotype 4b that spread nearly twice as much as the reference strain 10403S. No trends were observed regarding intracellular doubling times in iBMDM by comparing sources and serotypes; based on these results, intracellular growth seems to be determined by genetic characteristics of each strain. The cell death induced by some isolates after infection of iBMDM was Caspase 1 dependent, indicating that they induce pyroptosis. Some of these isolates also induced high INF production by iBMDM. Using primary macrophages, it was revealed that INF production was always STING dependent, and in some cases it is fully cGAS independent, partially cGAS dependent, or even mostly cGAS dependent. We have characterized L. monocytogenes isolates that could provide novel insight into infectivity of this pathogen that may not be revealed by studying common laboratory strains, demanding further analysis of their genomes and other experimental approaches to reveal the mechanisms associated with the most extreme phenotypes exhibited.